Edukasi Akupresur Pada Kasus Nyeri Kepala Di Praktik Mandiri Akupunktur Valdi Haris Gambir Jakarta Pusat - Fatimah Rahmawati; Yessy Widhi Astuti; Franciscus Xaverius; Fatimah Wahyu; Dachliana Wahyu; Siti Aliyah Latifah (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2026)
According to data from the Indonesian Ministry of Health in 2022, headache are one of the most common health complaints, affecting an estimated 60% or more of the general population. Based on preliminary observations and interviews with the manager of the Valdi Haris Acupuncture Independent Practice in Central Jakarta revealed that most people near the practice complain of headache and tend to immediately take painkillers without considering complementary therapies, such as acupressure. Acupressure, as a complementary therapy approach, offers a safe, effective, and sustainable alternative. However, public knowledge about acupressure for reducing headache intensity remains very limited due to a lack of understanding of the benefits and safety of acupressure therapy. This community service activity aims to provide acupressure education to the community at the Valdi Haris Acupuncture Independent Practice in Gambir, Central Jakarta, as a headache treatment. Data were collected through preparation, initial assessment, education, and acupressure demonstration phases involving participants with headache, as well as mentoring for independent practice. Evaluation through pre-test and post-test activities was also conducted. The results of the activity showed that all participants in the acupressure therapy education for headache followed the entire series of activities and understood the causes and efforts to prevent headache through mastering independent acupressure techniques, thereby increasing the participants' readiness to perform acupressure independently as an initial effort to treat headache safely and effectively.